Implementasi Manajemen Risiko pada Rencana Kerja dan Anggaran Perusahaan (RKAP) Studi Kasus Perusahaan Life Insurance - Muhammad Saentia Romana; Bramantyo Djohanputro; Lis Sintha (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Life Insurance companies prepare the Company Work Plan and Budget (RKAP) every year. The 2025 RKAP has been prepared according to the 2024 achievement prognosis with the strategy referring to the company's long-term plan (RJPP) 2025-2029. The company's achievements in the previous year using forecast data are used as a reference in preparing the RKAP. External factors of the company in the form of macroeconomic and socio-political conditions are factors that are considered. Then internal factors of the company such as premium income, claims, underwriting profit and others are also other considerations in preparing the 2025 RKAP. This study uses a qualitative method to calculate the risk probability assessment and the impact of risk on the RKAP work program in order to obtain a more comprehensive understanding of risk management. In managing the risk of the Company's Work Plan and Budget, the company must ensure that all company targets are in line with the Company's strategy and objectives. The risk mitigation program focuses on improving skills and operational efficiency. Training and mentoring programs are designed to strengthen the ability of insurance agents in sales through routine training and direct assistance from top sales leaders. In addition, the development of SOPs for prospect classification and marketing applications with intuitive fact-finding features helps optimize the prospecting and sales process. In terms of collaboration, special incentive schemes and specific KPIs are implemented to drive the effectiveness of join sales, with periodic evaluations to ensure optimal results. The synchronization of tariff and benefit systems is also enhanced through flexible modules and cross-functional collaboration. The implementation of the gatekeeper concept is supported by incentives for first-level providers and the integration of the application system with BPJS Kesehatan to ensure real-time data synchronization